Failure Mode and Damage Analysis of Concrete Structures - محمدرضا تابش پور; علی بخشی (مجله مدل سازی در مهندسی, 2007)
Abstract In order to investigate the performance of the buildings during earthquake it is necessary to perform nonlinear analysis to determine maximum deformations and plastic hinges distribution. Damage analysis is an appropriate method to seismic assessment of the structure. In this paper it is discussed on the results of the nonlinear static and dynamic analysis of the structures in seismic vulnerability. IDARC is used in structural modeling and analyses purposes.